A Pengenalan Kosakata Dasar Melalui Media Flascard Bergambar Pada Anak-Anak Desa Punie Kecamatan Darul Imarah Aceh Besar - Wina Almunadia Almunadia; Intan Munawarah; Anzora Anzora; Salsa Billa (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
This service is based on the low mastery of basic vocabulary among children in Punie Village, Darul Imarah District, Aceh Besar Regency. The lack of engaging learning media and suboptimal language stimulation for early childhood are the main factors that hinder children's vocabulary development. Picture flashcard media is considered an effective solution that can stimulate children's interest in learning while enriching their vocabulary through concrete and colorful visual imagery. The purpose of this service is to describe the effectiveness of using picture flashcard media in introducing basic vocabulary to children in Punie Village, Darul Imarah District, Aceh Besar. The method used in this research is descriptive qualitative with a community service approach. The research subject of devotion are children aged 5–10 years living in Punie Village. Data were collected through observation, interviews, and documentation during vocabulary introduction activities. The results of devotion show that the use picture flashcard media has a significant positive impact on children's ability to recognize and pronounce basic vocabulary. Children showed high enthusiasm, improved memory of new vocabulary, and better language skills after the activities were carried out. Picture flashcard media proved capable of creating a fun, interactive learning atmosphere that is appropriate to children's developmental characteristics.